2004
DOI: 10.1111/j.1440-1746.2004.03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection may be transmitted through blood transfusions in an endemic area

Abstract: Frequent transmission of HEV by blood transfusion places recipients at risk and warrants redefining of the donor screening policy by blood banks, especially in endemic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
4
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(168 citation statements)
references
References 23 publications
6
150
4
8
Order By: Relevance
“…Further, Kamar et al suggested that HEV infection in kidney transplant recipients is more severe that HCV infection [17][28]. Some studies have proposed blood transfusion as a potential route of HEV transmission, particularly in areas of high endemicity [14][15][29]. However, in this study, we did not find any correlation between a history of blood transfusion and HEV infection.…”
Section: Discussioncontrasting
confidence: 77%
“…Further, Kamar et al suggested that HEV infection in kidney transplant recipients is more severe that HCV infection [17][28]. Some studies have proposed blood transfusion as a potential route of HEV transmission, particularly in areas of high endemicity [14][15][29]. However, in this study, we did not find any correlation between a history of blood transfusion and HEV infection.…”
Section: Discussioncontrasting
confidence: 77%
“…A proportion of healthy blood donors in endemic regions have detectable HEV viremia and transfusion of their blood has been shown to lead to HEV infection among recipients. 50 Similarly, a proportion of babies born to mothers with acute hepatitis E during the third trimester of pregnancy have showed evidence of HEV infection in the form of detectable HEV RNA or IgM anti-HEV antibodies in cord blood. 51 However, the contribution of these routes to the overall burden of hepatitis E appears to be small.…”
Section: Reservoir Of Infection and Routes Of Transmissionmentioning
confidence: 99%
“…Eine retrospektive Untersuchung von Transfusionsempfängern lässt vermuten, dass HEV in Endemiegebieten durch Transfusion übertragen werden kann [180]. Zu einem vergleichbaren Schluss kommt eine weitere Studie, in der gezeigt wurde, dass Transfusionsempfänger nach der Transfusion Marker einer HEV-Infektion aufwiesen [181]. In Ägypten, einem Land mit einer hohen HEV-Antikörperprävalenz von bis zu 80 % in der ländlichen Bevöl-kerung, wiesen 2/760 Spenden (0,26 %) HEV-RNA auf [182].…”
Section: Prävalenz Und Inzidenz Bei Spenderkollektivenunclassified
“…Über transfusionsassoziierte HEV-Übertragun-gen wurde aus Saudi-Arabien berichtet, einem Land, in dem HEV-1 endemisch ist [181]. Erste Berichte aus Japan, das nicht als HEV-Endemiegebiet eingestuft wird, über transfusionsassoziierte HEV-Infektionen erfolgten etwa zeitgleich [188,190].…”
Section: üBertragbarkeitunclassified